Unravelling chromism in metal–organic frameworks. Issue 30 (23rd June 2017) - Mehlana, Gift; Bourne, Susan A.
Abstract : Chromophoric MOFs are reviewed, focussing on those which change colour on application of external stimuli such as heat, pressure, light or chemical environment. Abstract : This paper examines chromic metal–organic frameworks, an important class of materials owing to their applications in several technological fields. These materials change their absorption spectra upon application of an external stimuli such as heat, pressure, light etc. This review explores recent advancements in photochromic, thermochromic, solvatochromic, and piezochromic metal–organic frameworks (MOFs). Emphasis is directed towards the design of chromic MOFs as well as the mechanisms associated with the colour change upon application of an external stimulus. Compared to traditional organic and inorganic materials, MOFs show exceptional chromic behavior as they can be fine-tuned to tailor the desired properties.